The Investigation-Based Literature on the Reference Group and Buying Intention - M. Ilham Wardhana Haeruddin (Southeast Asia Journal of Business, Accounting, and Entrepreneurship, 2026)
Buying intention is a central construct in consumer behavior research because it bridges attitudes and the likelihood of action in markets. One of the most influential determinants of buying intention is the reference group—individuals or collectives that consumers use as a benchmark for beliefs, evaluations, and behaviors. This investigation-based literature review synthesizes theory and evidence on how reference groups shape consumer buying intention through mechanisms such as normative influence (pressures to comply), informational influence (belief formation via credible others), value internalization, and identity signaling. Drawing primarily on foundational perspectives from social psychology, consumer socialization, and marketing science, the review connects reference-group effects to established explanatory models including the Theory of Planned Behavior, Social Comparison Theory, and Self-Concept theories. It also integrates more recent developments such as online social influence and platform-mediated word-of-mouth, where visibility, algorithmic curation, and network dynamics alter how social cues are interpreted. Methodologically, the paper emphasizes an “investigation-based” approach: mapping constructs to testable propositions, contrasting causal pathways, and consolidating measurement strategies used in prior empirical studies. The review concludes that buying intention is shaped not only by whether consumers are influenced, but by how, when, and under what conditions influence becomes salient—particularly depending on product type, consumer involvement, cultural context, and trust in the reference source. The paper provides a research agenda for future experimental and longitudinal designs to refine causal inference.